Anthropometry profiles of elite rugby players: quantifying changes in lean mass. Issue 3 (27th February 2006) - Duthie, G M; Pyne, D B; Hopkins, W G; Livingstone, S; Hooper, S L
Abstract : Objective: To demonstrate the utility of a practical measure of lean mass for monitoring changes in the body composition of athletes. Methods: Between 1999 and 2003 body mass and sum of seven skinfolds were recorded for 40 forwards and 32 backs from one Super 12 rugby union franchise. Players were assessed on 13 (7) occasions (mean (SD)) over 1.9 (1.3) years. Mixed modelling of log transformed variables provided a lean mass index (LMI) of the form mass/skinfolds x, for monitoring changes in mass controlled for changes in skinfold thickness. Mean effects of phase of season and time in programme were modelled as percentage changes. Effects were standardised for interpretation of magnitudes. Results: The exponent x was 0.13 for forwards and 0.14 for backs (90% confidence limits ±0.03). The forwards had a small decrease in skinfolds (5.3%, 90% confidence limits ±2.2%) between preseason and competition phases, and a small increase (7.8%, 90% confidence limits ±3.1%) during the club season. A small decrease in LMI (∼1.5%) occurred after one year in the programme for forwards and backs, whereas increases in skinfolds for forwards became substantial (4.3%, 90% confidence limits ±2.2%) after three years. Individual variation in body composition was small within a season (within subject SD: body mass, 1.6%; skinfolds, 6.8%; LMI, 1.1%) and somewhat greater for body mass (2.1%) and LMI (1.7%) between seasons. Conclusions: Despite a lack of substantial mean changes, there was substantial individual variation in lean mass within and between seasons. An index of lean mass based on body mass and skinfolds is a potentially useful tool for assessing body composition of athletes.